A case of bacteremia caused by Slackia exigua in a patient with liver abscess, which caused by fish puncture through the stomach wall. (December 2022) - Zhang, Zhanfeng; Han, Tiantian; Lu, Weiguo; Zhou, Yingchun; Li, Danhua
Abstract: We present a case of hepatic abscess caused by a fish puncture through the gastric wall and the development of Slackia exigua infection. Highlights: It contributes to the awareness of this bacterium and provides clinical and laboratory evidence. It provides a clinical case for anaerobic infection. First time to report such case.